Sprague-Dawley大鼠肺发育中miR-431的连续表达研究 (Zhongguo Dang Dai Er Ke Za Zhi, 2019)
OBJECTIVE: To study the role of miR-431 in lung development and morphology. METHODS: According to the stage of lung development in rats, Sprague-Dawley rats at embryonic day 16 (E16), embryonic day (E19), embryonic day (E21), postnatal day 1 (P1), postnatal day 3 (P3), postnatal day 7 (P7), postnatal day 14 (P14) and 10 weeks after birth (P10 weeks) were selected, and lung tissue samples were collected for observation. Hematoxylin-eosin staining and transmission electron microscopy were performed to observe the morphology of lung tissue. Fluorescence in situ hybridization and real-time PCR were used to measure the expression of miR-431 during the critical stages of lung development (E19, E21 and P3). RESULTS: The E19 group had the formation of the lamellar body and type Ⅱ alveolar epithelial cells in the fetal lung tissue. The number of lamellar bodies increased with the increasing gestational age, with aggregation and excretion. Pulmonary alveoli formed rapidly, the lung interstitium became thinner, and the microvascular system became mature after birth. Fluorescence in situ hybridization and real-time PCR showed that the expression of miR-431 gradually decreased with the increasing gestational age (P < 0.05). CONCLUSIONS: The systematic and continuous morphological data of lung development is obtained in this experiment. In addition, miR-431 may play an important role in the negative regulation of lung development, which provides basis and direction for further research on the mechanism of lung development and related diseases.